Artificial Intelligence as Human Behavior Detection for Auto Personalization Function in Social Media Marketing - R D Santy; M I Habibillah; Y R Dimyati; V S. S. Nofia; S Luckyardi; T V. L. Gaol; D Oktafiani (Universitas Komputer Indonesia, 2021)
This study aims to determine how artificial intelligence's role in increasing marketing activities' effectiveness in automatic personalization. Some of the factors that can influence humans using social media are what they like, where they comment, and their type in the search fields on their social media. The method used in this research is a comparative descriptive method, namely describing or explaining and validating a phenomenon under study, then comparing it with other social media that has a different system. Some of the variables or objects studied in this paper are the user's habits in using social media and the artificial intelligence found on several social media that reacts with their users' habits. This study shows how artificial intelligence can increase the effectiveness of marketing activities on social media and produce comparable data between artificial intelligence technologies found in several social media, which shows that artificial intelligence is proven to increase marketing activities' effectiveness. It is done on social media.